(untitled) (Jahangirnagar University Journal of Biological Sciences, 2024)
Enhanced water, sanitation, and hygiene (WASH) conditions can significantly reduce the incidence of communicable diseases and deaths related to diarrhea by up to 65%. The US Centers for Disease Control and Prevention (CDC) advocates regular handwashing with soap and water for at least 20 seconds as an effective measure to mitigate the spread of COVID-19. This study aims to assess rural Bangladeshi households’ perceptions and knowledge concerning the COVID-19 pandemic, as well as their understanding, attitudes, and practices regarding water, sanitation, and hygiene. A cross-sectional study was conducted between June 2020 and December 2020 to evaluate knowledge and practices related to safe water, sanitation, personal hygiene, and COVID-19 in rural Bangladesh. Self-administered questionnaires, pre-tested for reliability, were utilized to collect self-reported data, which were subsequently analyzed descriptively. Of the study participants, 66.78% were female, with a mean age of 40. The majority (92.36%) demonstrated adequate knowledge of personal hygiene, although 66.78% had not received hygiene education, and a significant proportion reported low levels of hygiene practices (17.28%). Nearly all respondents (98%) reported having access to a pit latrine, either with or without a seal, yet 63.12% indicated that their toilets become unusable during floods, and 29% admitted to practicing open defecation. While nearly all respondents were aware of the ongoing COVID-19 outbreak, only 46% had a comprehensive understanding of its transmission dynamics. Moreover, knowledge about preventive measures against the pandemic was found to be limited. Despite understanding the importance of handwashing, reported hand hygiene practices were inadequate among rural households. Additionally, a majority reported inadequate management of child feces, household waste, and sludge tanks. While awareness of the COVID-19 pandemic was high, a substantial proportion of respondents lacked understanding of its transmission and prevention methods. Moreover, fewer respondents reported using hand sanitizer when venturing outside for work. Future research should explore the impact of these behaviors on health outcomes and propose targeted interventions to improve hygiene practices. Jahangirnagar University J. Biol. Sci. 12(1 & 2): 11-21, 2023 (June & December)